Lista przeorów karmelitów gdańskich w XVIII i XIX wieku - Puziak, Marcin (Studia Gdańskie, 2022)
In the literature on the subject, there are several lists of the priors of Gdańsk Carmelites created by older and newer researchers (Schwengel, Fankidejski, Kościelak, Januszjtis). However, they are incomplete. The article proposes to supplement this list for the period of the 18th-19th centuries. During this period, the Gdańsk convent belonged to the Greater Poland Province of the Blessed Sacrament. The files of the chapters and definitors of this province, today kept in the Carmelite Archives in Krakow, constitute the source basis for the analysis proposed here. The presented list of priors (and sub-priors) is supplemented with a series of general observations that characterize the monks performing this function in the basic prosopographic aspects. Several comments were also made about the circumstances of the changes at this office. Further research is postulated on the basis of the analyzed files, e.g. prosopographic, or the presence of the Gdańsk Carmelite community in local church and socio-economic structures.